2019
DOI: 10.1097/ccm.0000000000003975
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guidelines and Consensus Statements About Pain Management in Critically Ill End-of-Life Patients: A Systematic Review

Abstract: Objectives: To identify and synthesize available recommendations from scientific societies and experts on pain management at the end-of-life in the ICU. Data Sources: We conducted a systematic review of PubMed, EMBASE, the Cochrane Database of Systematic Reviews, and Biblioteca Virtual en Salud from their inception until March 28, 2019. Study Selection: We included all clinical practice guidelines, consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Doses reported in many of the reviewed documents were higher than recommended dosages in guidelines for critically ill patients at the end-of-life [3]. This could be explained by the development of opioid tolerance in a considerable proportion of critically ill patients who are at the end-of-life, as evidenced by one study in which more than half of patients were already receiving opioids prior to withholding or withdrawing of life support [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Doses reported in many of the reviewed documents were higher than recommended dosages in guidelines for critically ill patients at the end-of-life [3]. This could be explained by the development of opioid tolerance in a considerable proportion of critically ill patients who are at the end-of-life, as evidenced by one study in which more than half of patients were already receiving opioids prior to withholding or withdrawing of life support [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is homogeneity among end-of-life critical care guidelines, our systematic review showed a wide variation in practice and medication use, which could be attributed to the individualization of care recommended by guidelines, underuse of standardized protocols, or lack of guideline specificity in the recommendations [ 3 , 39 41 ]. Of note, among the more recent studies included in this review, we observed that the frequency of use was lower for morphine and higher for fentanyl compared to the earlier studies included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…80 A recent systematic review has highlighted the growing demand for the involvement of PC teams in the management of the dying patients in the ICU, the need to facilitate their early involvement, and to further develop comprehensive evidence-based pain management strategies. 81 A further complicating factor in the integration of PC in ICU practices is the fact that EoL care varies significantly between countries and health care systems. Practices and attitudes around death and dying are more hospital-centric in North America than in Europe but ICU admissions in the last days of life have the opposite distribution.…”
Section: Role Of Palliative Care In the Intensive Care Unitmentioning
confidence: 99%